Analisis Dampak Limbah Sampah Rumah Tangga Terhubung Pencemaran Lingkungan Hidup - Erika Erika; Eva Gusmira (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Household waste is one of the major environmental pollution issues that is increasing along with population growth and urbanization. This article aims to analyze the impact of household waste on environmental pollution, including air, soil, and water pollution. Furthermore, this article explores various solutions that can be applied to reduce these negative impacts. The research methodology includes a literature review and case studies in major cities in Indonesia. The findings indicate significant contributions of household waste to environmental degradation, emphasizing the need for integrated waste management, public awareness, and stringent regulations to mitigate these effect.